Membangun Keadilan Fiskal: Analisis Sederhana Tentang Subsidi dan Redistribusi - Saragih, Farid Maulana; Prasetya, Muhammad Daffa Adhie; Zein, Ahmad Wahyudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Fiscal justice is an important principle in creating equality and social welfare in society. Through subsidy and redistribution policies, the government seeks to help disadvantaged and vulnerable groups in society. However, in practice, the distribution of benefits from subsidies is often uneven. This article aims to provide a simple understanding of the concept of fiscal justice and examine the actual conditions of subsidies and redistribution programs in Indonesia. This study uses a descriptive-qualitative approach with a literature study. The results show that fiscal policy in Indonesia still faces challenges in targeting accuracy and efficiency. Recommendations are given for policy reform so that fiscal justice can truly be realized.